Characteristics of Ocean Currents in the Lembeh Strait, North Sulawesi - Rori, Jenever; Angmalisang, Ping Astony; Pelle, Wilmy Etwil; Kumampung, Deislie R. H.; Djamaaludin, Rignolda; Rampengan, Royke M (Jurnal Ilmiah Platax, 2023)
Current is a process of mass transfer of seawater that moves from one place to another continuously or occurs continuously. The current generation factor on the surface of the water is caused by two things, namely the wind and the movement of the rise and fall of sea level. The Lembeh Strait is an Archipelago Port Area and a hub port in Kawasan Timur Indonesia (KTI), as well as an area with local transportation routes for the community. For this reason, it is necessary to research to obtain information about the characteristics and patterns of currents that occur in the Lembeh Strait. This research was conducted using a database of currents and tide data over the period from 2021 to 2022. The research method used is quantitative. Data sources were taken from Badan Meteorologi Klimatologi dan Geofisika (BMKG) Stasiun Maritim Bitung and the Copernicus Marine Service website. These data were analyzed using methods that fit the needs of the data. Flow and Tidal data were analyzed using WRPLOT View, Ocean Data View, Microsoft Excel, and Origin Pro. The results of data processing show the direction and speed of the current as well as the relationship between the tides and currents in the waters of the Lembeh Strait. The scatter plot of currents on the surface layer of the sea is elliptical, this indicates that the currents that dominate in these waters are tidal. So the results of the study show that ocean currents in the Lembeh Strait have current characteristics that are dominantly influenced by tides and the dominant current direction is formed in 2021 and 2022 towards the Southwest and Northeast. Keywords: Current, Tidal Current, Lembeh Strait. Abstrak Arus merupakan proses pergerakan massa air laut yang berpindah dari satu tempat ke tempat lain secara kontinu atau terjadi secara terus-menerus. Faktor pembangkit arus di permukaan air disebabkan oleh dua hal yaitu angin dan pergerakan naik turunnya permukaan air laut. Selat Lembeh merupakan Kawasan Pelabuhan Nusantara dan sebagai salah satu hub port di kawasan Timur Indonesia (KTI), serta sebagai kawasan dengan alur transportasi lokal bagi masyarakat. Untuk itu perlu dilakukan penelitian guna mendapatkan informasi tentang karakteristik dan pola arus yang terjadi di Selat Lembeh.  Penelitian ini dilakukan dengan menggunakan basis data arus dan data pasang surut selang periode waktu dari tahun 2021 sampai dengan tahun 2022.  Metode penelitian yang digunakan adalah metode kuantitatif. Sumber data diambil dari instansi Badan Meteorologi Klimatologi dan Geofisika (BMKG) Stasiun Maritim Bitung dan dari Website Copernicus Marine Service. Data-data tersebut di analisis menggunakan metode yang sesuai dengan kebutuhan data. Data Arus dan Pasang Surut dianalisis menggunakan WRPLOT View, Ocean Data View, Microsoft Excel, dan Origin Pro. Hasil pengolahan data menunjukan arah dan kecepatan arus serta hubungan antara pasang surut dan arus di perairan Selat Lembeh. Scatter plot arus pada lapisan permukaan laut memiliki bentuk ellips, ini menunjukkan bahwa arus yang mendominasi di perairan tersebut adalah arus pasang surut. Sehingga hasil penelitian menunjukan arus laut di Selat Lembeh memiliki karakteristik arah arus dominan dipengaruhi oleh pasang surut dan diperoleh arah arus dominan terbentuk di tahun 2021 dan tahun 2022 menuju ke arah Barat Daya dan Timur Laut. Kata kunci : Arus, Arus Pasut, Selat Lembeh.